Enhanced biotransformation of starch to β-cyclodextrin by using high viability of immobilized Escherichia coli on hollow fiber membrane as whole cell biocatalyst - Baharudin, Nurul Nabila Huda; Che Man, Rohaida; Abdul Manas, Nor Hasmaliana; Abdul Mudalip, Siti Kholijah; Sulaiman, Siti Zubaidah; Mohd Arshad, Zatul Iffah (Science, Engineering and Health Studies, 2025)
Application of biological processes to chemocatalysis through biotransformation of a substrate with assistance of whole cells increases efficiency of the entire process. Cell’s ability to excrete enzymes into extracellular space is crucial in a process of whole cell biocatalysis. However, issues with cell lysis and stability are frequently encountered when using free cell biocatalysts, particularly Escherichia coli. In this study, cell immobilization was studied to overcome these bottlenecks. The effects of process parameters, such as agitation rate, concentration of substrate, temperature, pH, and reaction time, on the production of β-cyclodextrin (β-CD), the excretion of β-cyclodextrin glucanotransferase (β-CGTase), and cell lysis using immobilized recombinant E. coli on a hollow fiber membrane as whole cell biocatalyst were investigated. The optimum parameters were as follows: agitation rate, 200 rpm; starch, 4%; temperature, 40°C; reaction time, 4 h; and pH 6, with 5.25–6.14 mg/mL β-CD, 29.88–35.13 U/mL β-CGTase excretion, and 0.3–1.35 U/mL β-galactosidase activity. The immobilized cells exhibited a 11–14-fold increase in β-CD, 17–19-fold increase in β-CGTase excretion, and a 92% reduction of cell lysis compared with the free cells. Therefore, the high viability of the immobilized cell was considered valuable for the efficient biotransformation of starch to β-CD.